Pengaruh Kecerdasan Spiritual dan Motivasi Belajar terhadap Hasil Belajar Siswa Mata Pelajaran Al-Qur'an Hadis - Umi Muslikhah; Sugiyo (Fahima, 2022)
This study aims to determine the effect of spiritual intelligence on student learning outcomes in Al-Qur'an Hadith subjects, the impact of learning motivation on student learning outcomes in Al-Qur'an Hadith subjects, and the influence of spiritual intelligence and learning motivation on student learning outcomes in subjects Al-Qur'an Hadith at MTs Negeri 3 Sukoharjo for the 2020/2021 Academic Year. This research is quantitative. The population in this study were all students of MTs Negeri 3 Sukoharjo for the academic year 2020/2021, totaling 378 students. The sample of this study was 194 students of MTs Negeri 3 Sukoharjo for the academic year 2020/2021 with the sampling technique of proportionate stratified random sampling. This study uses two data collection techniques: a questionnaire (questionnaire) and documentation. The test instrument uses validity and reliability tests. Classical assumption test using normality test and linearity test. The data analysis technique used Multiple Linear Regression, F test, t test, and coefficient of determination (R2). The results showed that the influence of spiritual intelligence on student learning outcomes in Al-Qur'an Hadith subjects at MTs Negeri 3 Sukoharjo for the 2020/2021 academic year proved to have a significantly positive effect. The effect of learning motivation on student learning outcomes for Al-Qur'an Hadith subjects at MTs Negeri 3 Sukoharjo for the 2020/2021 academic year proved to have a significantly positive effect. The influence of spiritual intelligence and learning motivation on student learning outcomes in Al-Qur'an Hadith subjects at MTs Negeri 3 Sukoharjo for the 2020/2021 academic year proved to have a significant effect.